Emergence of canine parvovirus type 2c (CPV-2c) of Asian origin in domestic dogs in Myanmar. (November 2022) - Mon, Pont Pont; Thurain, Khin; Charoenkul, Kamonpan; Nasamran, Chanakarn; Wynn, Myint; Tun, Than Naing; Amonsin, Alongkorn
Abstract: Canine parvovirus type 2 (CPV-2) causes severe gastroenteric disease in domestic dogs and wild canids. This study aimed to conduct molecular detection and characterization of CPV-2 in domestic dogs in Myanmar from December 2017 to October 2019. Rectal swabs (n = 143) were collected from domestic dogs from shelters and small animal hospitals in Yangon, Myanmar. CPV-2 detection was performed by a PCR assay targeting the VP2 gene. Our result showed that 25.17% (36/143) of swab samples tested positive for CPV-2. CPV-2 strains (n = 15) were selected for complete VP2 gene sequencing. Phylogenetic analysis showed that CPV-2 strains from Myanmar clustered together with Asian CPV-2c from China, Indonesia, Taiwan and Thailand but in separate clusters from CPV-2c from Europe and North America. Characteristic amino acid at residues 267Y and 324I were observed in CPV-2c strains from Myanmar, suggesting the Asian origin. In conclusion, our findings expanded the evidence of the predominance of CPV-2c in Southeast Asia. Thus, the surveillance of CPV-2 in domestic dogs in the countries and regions should be routinely conducted to provide epidemiological information for supporting prevention and control practices. Highlights: An investigation of canine parvovirus type 2 (CPV-2) in domestic dogs in Myanmar from December 2017 to October 2019 showed that 25.17% (36/143) of rectal swab samples tested positive for CPV-2 by a PCR assay targeting the VP2 gene. Fifteen CPV-2 viruses were characterized by complete VP2 gene sequencing. Phylogenetic analysis showed that CPV-2 strains from Myanmar clustered together with Asian CPV-2c strains but in separate clusters from classical CPV-2c from Europe and North America. Amino acid at residues 267Y and 324I were observed in CPV-2c strains from Myanmar, suggesting the Asian origin. Our findings expanded the evidence of the predominance of canine parvovirus type 2c in Southeast Asia.